Development of a standardized definition of pulmonary embolism‐related death: A cross‐sectional survey of international thrombosis experts. (30th March 2020) - Tritschler, Tobias; Kraaijpoel, Noémie; Langlois, Nicole; Girard, Philippe; Schulman, Sam; Büller, Harry R.; Segers, Annelise; Righini, Marc; Le Gal, Grégoire
Abstract: Introduction: Pulmonary embolism (PE)‐related death is often part of the primary outcome in venous thromboembolism (VTE) studies. The Scientific and Standardization Committee (SSC) of the International Society on Thrombosis and Haemostasis developed a definition for PE‐related death and classification of the cause of death. The present survey evaluated a preliminary version of this definition and classification. Methods: Sixty‐nine VTE experts from nine countries were invited for a cross‐sectional online survey on January 15, 2019, including multiple‐choice and open‐ended questions on a seven‐subcategory classification of the cause of death. Descriptive statistics were used to describe the results; qualitative comments were summarized. Results: Forty of 69 (58%) invitees completed the survey. All respondents agreed that guidance on classification of the cause of death in VTE studies is required. There was high agreement on the proposal (median overall score, 6; interquartile range, 6‐7; scale from 1 [poor] to 7 [excellent]). All respondents approved the wording and content of the seven subcategories, except for one disagreeing vote for two subcategories (A3: "PE is not objectively confirmed, but is most likely the main cause of death" and C1: "Another cause of death is more likely than PE but has not been objectively confirmed"). Suggestions for improvement mainly concerned the extensiveness of the criteria and clinical situations described to define the cause of death. Conclusion: Acceptance of the proposal was excellent. Suggestions for improvement were incorporated in the SSC communication on the definition of PE‐related death and classification of the cause of death in VTE studies.